Categories and activities in the area of inclusion of people with disabilities found within commune strategies – selected examples based on the communes of the counties of Żywiec and Cieszyn districts - MRÓZEK, SEBASTIAN (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Sebastian Mrózek, Categories and activities in the area of inclusion of people with disabilities found within commune strategies – selected examples based on the communes of the counties of Żywiec and Cieszyn districts. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 29–52. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.02 The issue of strategies of activities aimed at people with disabilities living in the relevant communes is a topic rarely undertaken in discourse of special pedagogy. These issues are found among the other activities that local government entities are contemporary obligated to implement, and span solutions and activities in the area of inclusion for people with disabilities. It is hence important to know and overcome problems and barriers that hinder or block the right functioning of people with disabilities. Some of solutions and activities are contained in the two types of communal strategic documents, these are: Commune Development Strategies and Strategies for solving social problems. The article consists of three parts. The first covers the characteristics of communal strategies and social policy towards people with disabilities. The second part presents the assumptions and results of research based on a qualitative analysis of strategic documents of 27 communes (about 3900 pages of documents) in terms of categories and activities regarding the inclusion of people with disabilities. The whole is summarised in the final conclusions. The aim of the study is preliminary recognition of exemplary activities found in the strategies of communes from the counties of Żywiec and Cieszyn. Text notes the “good practices” and noteworthy solutions for inclusion applied by local government entities with respect to people with disabilities.